On the rotordynamic stability of two‐pole synchronous electric machinery considering different load cases. Issue 1 (25th October 2016) - Boy, Felix; Hetzler, Hartmut
Abstract: This paper discusses stationary rotordynamics of synchronous electric machinery, considering different load cases. The model comprises the electrical operation in a rigid network and in an isolated condition. The mechanical part is modelled as a Laval Rotor (Jeffcott Rotor) with a noncircular shaft, accounting for both static‐ and dynamic rotor eccentricities. The results show, that the machine's electrical operation may influence the occurence of mechanical vibrations significantly and therefore demonstrate the importance of analysing the electromechanical interaction. (© 2016 Wiley‐VCH Verlag GmbH & Co. KGaA, Weinheim)